Associations of mood, perceived stress, cognitive dietary restraint and the menstrual cycle in healthy New Zealand females : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - McKenzie, Caitlin (Massey University, 2025)
Background: Subclinical ovulatory disturbances (SOD) are the initial adaptations of the female reproductive axis to stress. Previous research suggests that psychological stressors, such as perceived stress and cognitive dietary restraint (CDR), may contribute to the occurrence of subclinical ovulatory disturbed cycles (SOD cycles) in healthy menstruating females; however, no studies have investigated these associations in the New Zealand context. The reduction in sex steroid hormones that occurs with SOD cycles may also contribute to variations in psychological factors throughout the menstrual cycle. Although previous research has investigated changes in mood and perceived stress between menstrual cycle phases, mixed results have been reported between studies and none have considered the ovulatory status of participants when investigating these changes. Therefore, the primary aim of the present study was to determine if females who presented with at least two SOD menstrual cycles (anovulation or luteal phase defects) displayed higher perceived stress and CDR than females who presented with at least two ovulatory menstrual cycles over a three-cycle period. A secondary aim was to investigate if there were variations in mood, perceived stress and CDR throughout the menstrual cycle in females with different menstrual cycle presentations (ovulatory versus SOD cycles). Methods: Ninety-seven naturally menstruating females aged 30.5 ± 5.6 years participated in this prospective cohort study over five menstrual cycles. Participants completed the Profile of Mood States Questionnaire (POMS-Q), Perceived Stress Scale (PSS) and the Three Factor Eating Questionnaire (TFEQ) to measure mood, perceived stress and CDR during the early follicular, late follicular and mid luteal phases of the menstrual cycle. Urinary luteinising hormone testing and mid-luteal phase plasma progesterone levels were measured to classify cycles as ovulatory (mid-luteal progesterone > 10 nmol/L) or SOD (mid-luteal progesterone ≤ 10 nmol/L) and to verify menstrual cycle phase. Two-tailed independent samples t-tests were used to compare mean perceived stress and CDR scores between ovulatory and SOD participants. Linear mixed models with participants as the random effect and baseline gynaecological age, percentage body fat and scaled metabolic equivalent of task (MET) minutes per week were used to analyse the effects of menstrual cycle phase, ovulatory status and their interaction on scores of mood, perceived stress and CDR. Results: The average perceived stress score of all females was 24.7 ± 5.5 and the average CDR score was 14.0 ± 4.1. There was no difference in perceived stress (t = 0.5, df = 84, p = 0.606) or CDR (t = 1.7, df = 84, p = 0.100) scores between ovulatory (n = 68) and SOD (n = 18) groups. Furthermore, linear mixed models showed no individual or interaction effects of menstrual cycle phase and ovulatory status on mood, perceived stress or CDR (p > 0.006 for all variables). Conclusion: The results of this study suggest that healthy menstruating females presenting with at least two SOD cycles may not have higher perceived stress or CDR than females presenting with at least two ovulatory cycles over a three-cycle period. Furthermore, no group-level effects of menstrual cycle phase and ovulatory status on mood, perceived stress or CDR were observed. However, large inter-individual variability was seen throughout the menstrual cycle. Further research is needed to develop and improve methods used in menstrual cycle research.
Figure 2.1 is reproduced under a Creative Commons Attribution 4.0 International license (CC BY 4.0).
Keywords: 321004 Nutritional science